Novel cryopreservation medium for enhanced stability of T cells at −80°C - Zhou, WenXuan; Wang, Chen; Shi, Yao; Pan, Yi; Meng, XiaDuo; Kang, XunLei; Han, Xu (Frontiers in Hematology, 2024)
The increasing demand for immune cell applications, both in clinical settings and in research laboratories, has highlighted the critical need for cryopreservation (banking) methods for T cells. While conventional techniques such as freezing with liquid nitrogen remain prevalent, they pose significant challenges including high equipment costs, safety considerations, and logistical hurdles in transportation. Our cryopreservation medium, C80EZ®, represents a novel approach, leveraging biocompatible polysaccharides as cryoprotectants to enable safe storage at −80°C. This paper presents a comprehensive series of tests assessing the effectiveness of C80EZ® in shielding T cells from the detrimental effects of cryopreservation. Importantly, our findings demonstrate that C80EZ® not only ensures the survival of T cells, with a particular emphasis on preserving the CD8+ subsets, but also maintains their critical function in targeting and eliminating cancer cells.